Preliminary characterization of the etiologic agent causing zebra chip symptoms in potato - De Boer, Solke H; Secor, Gary; Li, X; Gourley, J; Ross, P; Rivera, Viviana (MTT, 2007)
A new disease of potato characterized by severe internal necrosis of tuber tissue was first observed in Mexico in 1994 and since 2000 has been observed in Guatemala, and several potato growing areas in the southern United States. Affected tubers are unmarketable because of severe discoloration throughout the tuber flesh, and when processed into chips (crisps) display bands of darkened tissue from which arose the common designation of zebra chip for this condition. In affected geographic regions, zebra chip has become a leading cause for rejection of potatoes for consumption and processing. Whether or not the appearance of this disease and its northward spread is related to changes in weather patterns associated with global warming is uncertain, but its appearance and spread is of increasing concern to the potato industry. Zebra chip-infected tubers often fail to sprout or when they do, produce hair sprouts and weak plants. Current season infection with zebra chip is associated with foliar symptoms that resemble those typically caused by phytoplasma. Despite the similarity of zebra chipassociated symptoms to phytoplasmal diseases, phytoplasma cannot be consistently detected in infected plants by the polymerase chain reaction (PCR) using standard procedures. Only the potato psyllid, Bactericerca cockerelli, has been consistently associated with disease incidence and spread. Psyllid salivary toxins, however, are not implicated in the disease etiology as the disease has been successfully graft transmitted in greenhouse trials. Transmission electron microscopy studies revealed the presence of bacteria-like organisms (BLOs) in the vascular tissue of infected plant parts that in appearance are similar to phloem-restricted BLOs associated with the basses richesses syndrome of sugar beets. To amplify purported BLO DNA, DNA template extracted from zebra chip-infected potato tubers was amplified with primers initially used to investigate phloem cucurbit yellow vine disease and marginal chlorosis of strawberry. While the primers that amplified DNA from strawberry BLO (subsequently identified as Ca. Phlomobacter fragariae) did not amplify specific DNA fragments, the primers that amplified DNA from the cucurbit BLO (subsequently identified as an atypical strain of Serratia marcescens) specifically amplified a 690 bp product from zebra chip-infected tuber tissue extracts. This fragment was cloned, sequenced, and blasted against the Genbank database. Identical sequences were not identified but the amplicon had a similarity of >97% to various enteric bacteria originating from diverse environmental plant and insect sources. Currently a genetic library of eubacterial rrn operons amplified with universal rrn primers from zebra chip-infected tubers is being constructed to evaluate the entire endophytic prokaryote community associated with the disease. Attempts to isolate zebra chip-associated bacteria on media designed for fastidious microorganisms are also ongoing.
Keywords: Ka; zebra chip; phytoplasma; bacteria-like organism; phloem-limited bacteria